The effect of heat treatment on the compressive strength of cement-slag mortars - Razak, Hashim Abdul; Sajedi, Fathollah (Elsevier, 2011)
Thirty-eight mix proportions of ordinary Portland cement-slag mortars (OSMs) were used to study the effects of temperature and relative humidity on strength. Three levels of slag (0, 40, and 50) and different temperatures were used; the 50 level and heat curing of 60 Â°C for duration of 20. h were found to be the optimum. The optimum mortar's strength at 3 and 7. days for the specimens cured in air were 55.0 and 62.0. MPa, respectively. The results show that for durations of 4-26. h, the strength of specimens cured in air is greater than those cured in water. This is a novelty with major advantages in arid areas. It was proved that more ettringite production at early ages resulted in higher early strengths. Comparison of curing regimes with different temperatures and the same relative humidity or different relative humidity and the same temperatures showed that higher strengths are attributed to higher temperatures and lower relative humidity, respectively. Â© 2011 Elsevier Ltd.